Asymmetric dumbbell-shaped silver nanoparticles and spherical gold nanoparticles green-synthesized by mangosteen (Garcinia mangostana) pericarp waste extracts - Park JS (Dove Medical Press, 2017)
Ji Su Park, Eun-Young Ahn, Youmie Park College of Pharmacy, Inje Institute of Pharmaceutical Sciences and Research, Inje University, Gimhae, Gyeongnam, Republic of Korea Abstract: Mangosteen (Garcinia mangostana) pericarp waste extract was used to synthesize gold and silver nanoparticles by a green strategy. The extract was both a reducing and stabilizing agent during synthesis. Phytochemical screening of the extract was conducted to obtain information regarding the presence/absence of primary and secondary metabolites in the extract. The in vitro antioxidant activity results demonstrated that the extract had excellent antioxidant activity, which was comparable to a standard (butylated hydroxy toluene). Spherical gold nanoparticles (gold nanoparticles green synthesized by mangosteen pericarp extract [GM-AuNPs]) with an average size of 15.37±3.99 to 44.20±16.99 nm were observed in high-resolution transmission electron microscopy (HR-TEM) images. Most interestingly, the silver nanoparticles (silver nanoparticles green synthesized by mangosteen pericarp extract [GM-AgNPs]) had asymmetric nanodumbbell shapes where one tail grew from a spherical head. The average head size was measured to be 13.65±5.07 to 31.08±3.99 nm from HR-TEM images. The hydrodynamic size of both nanoparticles tended to increase with increasing extract concentration. Large negative zeta potentials (–18.92 to –34.77 mV) suggested that each nanoparticle solution possessed excellent colloidal stability. The reaction yields were 99.7% for GM-AuNPs and 82.8% for GM-AgNPs, which were assessed by inductively coupled plasma optical emission spectroscopy. A high-resolution X-ray diffraction pattern confirmed the face-centered cubic structure of both nanoparticles. Based on phytochemical screening and Fourier transform infrared spectra, the hydroxyl functional groups of carbohydrates, flavonoids, glycosides, and phenolic compounds were most likely involved in a reduction reaction of gold or silver salts to their corresponding nanoparticles. The in vitro cytotoxicity (based on a water-soluble tetrazolium assay) demonstrated that GM-AgNPs were toxic to both A549 (a human lung cancer cell) and NIH3T3 (a mouse fibroblast cell). The cytotoxicity of GM-AgNPs on A549 cells was related to apoptotic cell death. However, GM-AuNPs did not show any significant cytotoxicity to either cell. These results suggest that GM-AuNPs have the potential to be drug delivery vehicles or carriers for pharmaceutical and biomedical applications. Keywords: mangosteen pericarp extracts, Garcinia mangostana, green synthesis, gold nanoparticles, silver nanoparticles, asymmetric silver nanodumbbells, cytotoxicity, apoptosis, A549 human lung cancer cell, NIH3T3 mouse fibroblast cell